Letter from Max Bredig to Kasimir Fajans, August 21, 1937 - Bredig, Max Albert (1937)
Max Albert Bredig (1902-1977) requests an affidavit from Kasimir Fajans (1887-1975) and updates him on his travel plans to the United States. He has a ticket on the S.S. Bremen for October 1, 1937. He plans on arriving in Ann Arbor, Michigan on October 12, 1937.
Keywords: Bredig, Max Albert, 1902-1977; Fajans, Kasimir, 1887-1975; Emigration and immigration; Chemists; Bredig, Georg, 1868-1944